"Once upon a time...". (1st October 2021) - Taylor, Mike
Abstract : Representations of data have evolved considerably in the last 20 years: in terms of the scale of the data we have, the ways in which we can communicate and the expectations of our audiences. But as our tools evolve, so we have to evolve our understanding of what we're doing, the limitations, strengths or weaknesses and how we can use visualization to support our insights and narratives.